2017
DOI: 10.1007/s41252-017-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of the Experiences of Minority Parents of Children with Autism Spectrum Disorder

Abstract: The purpose of this study is to explore the experience of minority parents' related to raising a child with autism spectrum disorder (ASD), with a specific focus on difficulties within communication and adaptation. Culturally and linguistically diverse families are under-represented in the literature concerning family adaptation to a child with ASD and present specific challenges for healthcare providers in providing care for families. The study involved qualitative analysis of focus groups with six culturally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Understanding the needs of parents of children with autism also has implications for decreasing parenting stress and improving the psychological well-being of parents (Hartley & Schultz, 2015). For this reason, a good number of studies focus on parental perspectives (e.g., Chu et al, 2020; Hall et al, 2017; Yaacob et al, 2021). Notwithstanding this, a great deal of literature in the field of autism, particularly that focusing on parents, tends to be deficit driven, that is, with a focus on “measuring” negative experiences of families (Potter, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the needs of parents of children with autism also has implications for decreasing parenting stress and improving the psychological well-being of parents (Hartley & Schultz, 2015). For this reason, a good number of studies focus on parental perspectives (e.g., Chu et al, 2020; Hall et al, 2017; Yaacob et al, 2021). Notwithstanding this, a great deal of literature in the field of autism, particularly that focusing on parents, tends to be deficit driven, that is, with a focus on “measuring” negative experiences of families (Potter, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of accurate knowledge of autism was affected by many factors, including cultural beliefs and practices. Cultural beliefs affected how parents perceived the symptoms of ASD, thereby determining their subsequent responses [5]. Many of these parents perceived the child's symptoms as acceptable and falling within the bounds of normalcy, thereby delaying the search for relevant information about autism [24].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from previous studies have also shown that the presence of children with ASD in the family influences different aspects of parental and family life, such as marital relationships, sibling relationships, family socialization patterns, and daily routine [4]. Furthermore, a review of the literature revealed that parents with children who have ASD experienced higher stress levels [2,5] and anxiety and depression [6], felt isolated [7,8], and had a decreased quality of life [9] compared with parents of a normally developing child [10] or one with other disabilities, such as Down Syndrome [11]. These issues were compounded by the child's maladaptive behaviors, regular outbursts, hyperactivity, aggression, repetitive behaviors, and lack of social interaction [4].…”
Section: Introductionmentioning
confidence: 99%